ChemInform Abstract: Hypervalent‐Iodine(III)‐Mediated Oxidative Methodology for the Synthesis of Fused Triazoles. Issue 38 (1st September 2016) - Kamal, Raj; Kumar, Vipan; Kumar, Ravinder
Abstract: Review: 93 refs.